PENERAPAN APLIKASI CERDAS PENCEGAHAN STUNTING DI POSYANDU ARUMDALU DESA SANGGRAHAN GROGOL SUKOHARJO - Sari, Devi Pramita; Widodo, Sri; Mustofa, Khoirul; Januar Isnaini, Vina; Muhammad Darmawan, Diki (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is a condition of failure to achieve normal growth due to poor nutritional status over a long period of time. The purpose of this Community Service Program is to increase the knowledge of stunting cadres through smart applications for stunting prevention. This is the basis for community service with the title "PKM Implementation of Smart Applications for Stunting Prevention at the Arumdalu Integrated Health Post (Posyandu) in Sanggrahan Village, Grogol, Sukoharjo". The activity stages begin with coordination and communication activities with the Village Head, Village Midwife, and the Chairperson of the Arumdalu Integrated Health Post (Posyandu) in Sanggrahan Village. The implementation of Community Service (PKM) is carried out offline through digital-based education with a brainstorming method. The outputs of this PkM activity are the publication of scientific articles in the PkM journal, proceedings, posters, mass media publications, application guides, 5-minute PkM activity videos, and the integration of PkM activity results into courses. The outputs of this PkM are expected to have an impact on increasing knowledge, improving the quality of abilities, and real practices of the Arumdalu Integrated Health Post (Posyandu) cadres in Sanggrahan Village in stunting prevention.